CONFLICT AMONG PARTIES IN MODERNIZATION OF ECOSYSTEMS AT SUBAKS LOCATED IN BULELENG AND TABANAN REGENCIES OF BALI AT IRRIGATED BY SHABA RIVER - Arthanegara, I Nyoman; Ardika, I Wayan; Bawa Atmaja, Nengah; Sutawan, Nyoman (E-Journal of Cultural Studies, 2012)
Conflict among parties of subak ecosystem is a conflict of interests resulting from themodernization made by political community with regard to the subculture ofpelemahan of ecosystem. The political and economic communities forcemodernization on the subak ecosystem leading to an ideological conflict betweenmodernism and the philosophy of Trihita Karana. Modernism has been responsiblefor the conflict among the parties of ecosystem in palemahan, pawongan andparhyangan of the subaks irrigated by Sabha River.Participation in group discussion, semi structured interview and transek were themethods employed in collecting the data. The triangulation including at least threerelevant theories was employed for analyzing the data.Political communities interfere with the development by applying the theoryof hegemony. The political community in collaboration with the economic communitydominates modernization which is sectoral in nature and the planning andimplementation of the development. Partial development approach, which contrastswith the theory of ecosystem (Pollunin, 1996), causes the farming community lifeprocess and the cultural values existing in the ecosystem of the subak to degrade. Theinterference of the political community in collaboration with the economiccommunity with the subak ecosystem is more dominant in the subculture ofpalemahan which is materialistic in nature so that advantages can be obtained byscience and technology. Consequently, the philosophical values of trihita karana arebroken. Such a conflict takes place due to the different interests in the subakecosystem , which is full of cultural values for the farming community. Alteration tothe land status, the imbalance between the cost spent and the yields produced and theviolation of the growing pattern are responsible for the conflict.The institution of subak, which constitutes the realization of subculture of thesubak ecosystem, is swept aside by the political and economic communities. Thefarming community members that are the members of the subak institution are madenot to be facilitated to take part in the development process in the subculture ofpalemahan . Modernization in the subculture of palemahan of the subak ecosystemdone by the political and economic communities is beyond the subak institutioncausing it to violate the traditional values of the subak institution which refer totogetherness regulated by the subak rules and regulations. Modernization, which isdone by the political and economic societies by science and technology, breaks theunified existence of Trihita Karana in the subak ecosystem environment.Modernization in the development of the subculture of palemahan ecosystem degrades the spiritual values attached to the subculture of parahyangan. Thedevelopmental intervention in the subculture of palemahan done by the political andeconomical communities is not begun from the implementation of the subculture ofparahyangan. This contrasts with the cultural values existing in the subak ecosystem.The conflict of subak ecosystem among the parties results from the failure ofmodernization. The developmental intervention is only done in the subculture ofpalemahan, while the subcultures of pawongan and parahyangan of the subakecosystem are marginalized from their habitats. The failure in developing theinfrastructure of the subculture of palemahan of the subak ecosystem in the areasirrigated by Sabha River results from the fact that the subaks are functioned to be thedevelopmental objects. In this case, the theory of participatory can offer solutions tothe conflict and the developmental failure, especially in the ecosystem of subaksirrigated by Sabha River. The reason is that the parties play equal roles in developingthe environment of the subak ecosystem.
Keywords: sustainable, ecosystem, conflik, stakeholder, participatory and eguallity